Implementasi Model Pembelajaran Inovatif dalam Pengembangan Jiwa Kewirausahaan Peserta Didik di Lingkungan Pendidikan - Wahira Wahira; Andi Ratu Ayuashari (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The rapid development of globalization and technology has encouraged educational institutions to develop students’ entrepreneurial competencies through innovative learning approaches. Conventional teacher-centered learning is considered less effective in fostering creativity, critical thinking, and problem-solving skills needed in entrepreneurship education. This study aims to analyze the implementation of innovative learning models in developing students’ entrepreneurial spirit within educational environments. The study employed a qualitative descriptive approach through literature review and analysis of various innovative learning models applied in entrepreneurship education. The discussion focused on the implementation of Problem Based Learning (PBL), Project Based Learning (PjBL), Flipped Classroom, Blended Learning, Cooperative Learning, and Collaborative Learning in supporting entrepreneurial learning processes. The findings revealed that innovative learning models provide positive contributions to increasing students’ motivation, creativity, independence, collaboration skills, and entrepreneurial problem-solving abilities. Furthermore, the implementation of these models enables students to gain direct learning experiences through practical and contextual activities aligned with real-world challenges. This study contributes to the development of entrepreneurship education literature by providing a comprehensive understanding of how innovative learning models enhance students’ entrepreneurial competencies, including creativity, critical thinking, problem-solving, collaboration, and business opportunity recognition. Furthermore, the findings offer practical implications for educators and educational institutions in designing student-centered entrepreneurship learning environments that foster entrepreneurial mindsets and skills. The study also serves as a reference for policymakers in developing educational strategies that align with the demands of the twenty-first century and the evolving world of work [Perkembangan globalisasi dan teknologi yang sangat pesat mendorong lembaga pendidikan untuk mengembangkan kompetensi kewirausahaan peserta didik melalui pendekatan pembelajaran yang inovatif. Pembelajaran konvensional yang berpusat pada guru dinilai kurang efektif dalam menumbuhkan kreativitas, kemampuan berpikir kritis, dan keterampilan pemecahan masalah yang dibutuhkan dalam pendidikan kewirausahaan. Penelitian ini bertujuan untuk menganalisis implementasi model-model pembelajaran inovatif dalam mengembangkan jiwa kewirausahaan peserta didik di lingkungan pendidikan. Penelitian ini menggunakan pendekatan deskriptif kualitatif melalui studi literatur dan analisis berbagai model pembelajaran inovatif yang diterapkan dalam pendidikan kewirausahaan. Pembahasan difokuskan pada implementasi Problem Based Learning (PBL), Project Based Learning (PjBL), Flipped Classroom, Blended Learning, Cooperative Learning, dan Collaborative Learning dalam mendukung proses pembelajaran kewirausahaan. Hasil penelitian menunjukkan bahwa model-model pembelajaran inovatif memberikan kontribusi positif terhadap peningkatan motivasi, kreativitas, kemandirian, kemampuan kolaborasi, serta keterampilan pemecahan masalah kewirausahaan peserta didik. Selain itu, penerapan model-model tersebut memungkinkan peserta didik memperoleh pengalaman belajar secara langsung melalui kegiatan praktis dan kontekstual yang sesuai dengan tantangan dunia nyata. Penelitian ini berkontribusi pada pengembangan literatur pendidikan kewirausahaan dengan memberikan pemahaman yang komprehensif mengenai bagaimana model pembelajaran inovatif dapat meningkatkan kompetensi kewirausahaan peserta didik, termasuk kreativitas, berpikir kritis, pemecahan masalah, kolaborasi, dan kemampuan mengenali peluang usaha. Lebih lanjut, temuan penelitian ini memberikan implikasi praktis bagi pendidik dan institusi pendidikan dalam merancang lingkungan pembelajaran kewirausahaan yang berpusat pada peserta didik guna menumbuhkan pola pikir dan keterampilan kewirausahaan. Penelitian ini juga dapat menjadi referensi bagi para pengambil kebijakan dalam mengembangkan strategi pendidikan yang selaras dengan tuntutan abad ke-21 dan dinamika dunia kerja yang terus berkembang.]